Crystal Structure Refinements of the Lead(II) Oxoarsenates(V) Pb2As2O7, Pb(H2AsO4)2, Pb5(AsO4)3OH and NaPb4(AsO4)3 from Single-Crystal X-ray Data - Matthias Weil (MDPI AG, 2021)
Single-crystals of lead(II) oxoarsenates(V) were grown from the melt (Pb2As2O7), from solution (Pb(H2AsO4)2 and Pb5(AsO4)3OH), and under hydrothermal conditions (NaPb4(AsO4)3). Crystal structure refinements from single-crystal X-ray diffraction data revealed isotypism for both Pb2As2O7 and Pb(H2AsO4)2 with the corresponding barium and phosphate phases. A quantitative comparison of the crystal structures showed a high similarity for the isotypic M2X2O7 structures (M = Pb, Ba; X = As, P), whereas for the M(H2XO4)2 structures only the pair Pb(H2AsO4)2 and Pb(H2PO4)2 is similar, but not Ba(H2AsO4)2. Pb5(AsO4)3OH adopts the apatite structure type in space group P63/m, with the hydroxyl group disordered around Wyckoff position 2 b (0, 0, 0) in the channels of the structure. NaPb4(AsO4)3 represents a lacunar apatite with two of the three metal positions occupationally disordered by Pb and Na. In contrast to a previous X-ray powder study of NaPb4(AsO4)3 that reported an apatite-type structure in space group P63/m, the current single-crystal data clearly revealed a symmetry reduction to space group P<semantics><mover accent="true">3¯</mover></semantics>. Hence, NaPb4(AsO4)3 is the first lacunar apatite that comprises only tetrahedral anions and adopts the belovite structure type.